التحليل الجغرافي لظاهرة تعاطي المخدرات لدى الاحداث في محافظــة واســـط ( دراسة في جغرافية السكان) - عبد الحسن عجيل وسام (Journal of College of Education, 2019)
The phenomenon of taking drugs is considered as a social phenomenon which refers to the imbalance in the social and educational systems of the society, especially as it lies in within the class of the teenagers, which cause worry as this phenomenon has an effect which is not limited to the individual who takes drugs but it goes beyond this as its effect extends to the family and the society as a whole.Taking drugs by the teenagers is considered as one of the most important problems which the society faces in Wasit governorate which started to extend because of the security, economical, and social situation after 2003 and the events that came after. The danger of this problem is clear as it affects the young teenagers and impede the achievements of the goals of the human development by depriving them from the right to live in peace and the right to learn because of what the society suffer from as the high unemployment rates and the low standards of living of the families as most of them live n random and an organized areas and this force this class to enter the labor market and acquire abnormal behaviors and acts such as stealing, taking drugs and alcohol and committing moral crimes which is a real danger of the society. The study reached to explain the effect of the economical, social, and psychological factors and showing the implications of taking drugs by the teenagers.